Dusts Control operations in Ririwai Mines, Kano State, Nigeria (Indian Journal of Management and Language (IJML), 2024)
Respirable dust is everywhere (in the surface and underground mine) operations and its environs. Ririwai Tin mine is laden with dust of metallic particles of Arsenic (As), Chromium (Cr), Lead (Pb) and Zinc (Zn). These particles are also found in the soil. Continuous inhalation of dust could lead to irreversible diseases. This paper addresses the control of dust, using previous review of prevailing metallic concentrates. This research answers questions like which are the dust control strategies to be adopted by Ririwai tin mine to obtain best practice? What challenges will Ririwai tin mine face when applying dust control methods in their operation? What is the impact of dust laden with metallic particles on soil, water, vegetation and man in Ririwai tin mine?